Product Market Competition, Corporate Governance and ESG - Siti Nurain Muhmad; Akmalia M. Ariff; Norakma Abd. Majid; Khairul Anuar Kamarudin (Asian Academy of Management Journal of Accounting and Finance, 2021)
This paper examines whether product market competition is associated with Environmental, Social, and Corporate Governance (ESG) and whether corporate governance moderates the effect of product market competition on ESG. Analysis involving 22,897 firm-year observations from 37 countries shows that companies with higher product competition have lower ESG and those with higher corporate governance have higher ESG. The results also indicate the moderating effect of corporate governance, as the negative relationship between product market competition and ESG diminishes for companies with higher corporate governance. The results remain robust in additional analysis using alternative measures for product market competition and corporate governance. The findings support the joint effect of product market competition and corporate governance in determining corporate performance in ESG. The findings reflect the various pressures influencing ESG practices, and on how the strength of corporate governance plays a vital role in ensuring strategic ESG being employed for the sustainable performance of companies. The findings have implications on companies that want to factor ESG into their plans especially to reinvent their companies for the period that follows the COVID-19 pandemic.